(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
Cultivating mung bean for green manure and plowing into the soil before sowing winter wheat and thereby increase the yield of winter wheat and the humus content in the soil is the main goal of our field experiment.